Pre-treatment optimization of Scenedesmus obliquus microalga for bioethanol production - Miranda, J. R. (2013)
The present work deals with the optimization of cellular disruption and sugar extraction from the microalgae Scenedesmusobliquus (Sc) for bioethanol production. Among the physical and physicochemical methods tested, the best results were obtained with acid hydrolysis by H2SO4 (2 N), at 120 °C for 30 min and using dried biomass. The sugar extraction efficiency level reached was 95.6% when compared to the harsh quantitative acid hydrolysis. The influence of other parameters such as biomass loading and number of extraction cycles were also evaluated. The results obtained in the latter case showed that a unique hydrolysis step is sufficient.